As trabalhadoras do Banco Comunitário de Desenvolvimento Nascente: reflexões sobre políticas públicas de economia solidária, incubação universitária e a autonomia das mulheres - Schwenck, Beatriz Carrascosa von Glehn (2018)
This research is positioned between two different lines of thought: one that denunciates current forms of operationalization of the social matter as forms of control, and the other that presents Politics related to certain forms of surpassing poverty, amongst them Solidarity Economy in general and, more specifically, Community Development Banks. Here are some thoughts about women’s place in public life as ways for treating poverty that transform the economy and also contribute to the construction of women as subjects of rights, capable of exposing their dilemmas and vindicating their rights. This work aims to explore the impacts of a public policy for surpassing poverty based in solidarity economic principles in the daily life of its beneficiary parties, for their emergence as political subjects. Therefore, with a foundation in the methodology of the research-action, I present my experience with the activities developed in a Community Development Bank named Banco Comunitário de Desenvolvimento Nascente, located in São Carlos-SP-Brazil, and the experience I shared with the working women of this enterprise, the local development agents.